Germination and Early Seedling Growth of Three Arabica Coffee Varieties at Four Seed Soaking Water Temperatures - Wibowo, Ari; Aprillia Wijaya, Stefani; Suharjono, . (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
It takes three weeks to analyze the germination percentage of Arabica coffee seeds germinated using paper and a three-day water-soaking method. This 3- week period is considered too long for seed distribution to remote areas. Thus, we need to modify this germination test needs to be modified to have a shorter test time. Temperature treatment is one method to break the seed dormancy period for faster germination. This study aimed to obtain a faster and more precise method of germination test on Arabica coffee seeds. This study employed a 3 x 4 factorial complete randomized block design with three replications in which Arabica coffee varieties of Gayo-1, Kartika-1, and Sigararutang as the first factor and the temperature of the soaking water of the seeds (25 0C, 50 0C, 75 0C, and 90 0C) as the second factor. The research was conducted at the Plant Breeding Laboratory, Indonesian Coffee and Cocoa Research Institute (ICCRI), for four months. Findings showed that the interaction between treatments was only found in seed germination percentage. Soaking in room temperature water (control) for three days was better than using water at 50 0C, 75 0C, and 90 0C on the germination percentage, sprout length, and vigor index. Observations of Arabica seed germination could be shortened to 14 days compared to the standard 21-day observation. During the seedling phase, the shoot growth and root growth of the Arabica coffee seeds soaked in water at 50 0C showed no significant difference from the control. Soaking at 75 0C and 90 0C damaged the embryo and resulted in rotten seeds. Different varieties led to different germination percentages, sprout lengths, and fresh weight of seedling shoots. The method of soaking at 50 0C for 30 minutes could be used as an alternative in germination test of Arabica coffee seeds because it showed small negative effect on germinated seed and seedling quality but it shorten thetesting time for three days.